Extreme Accuracy : Long Range Rifle Shooting Techniques: big game Volume III, Shotgun - Tubb, G. David; Eveland, Brian; Lenny Magill Productions (Firm); Mail Order Video (Firm) (San Diego, CA : Lenny Magill Productions : [Distributed by] GunVideo, 1998)
Finally, a program that addresses the special requirements of big game hunters. It is vital that big game hunters improve their shooting skills because they usually have one chance to make a shot successfully.
Compact dicc
Keywords: Shooting positions; What makes a good huting rifle; Understanding your ammunition's ballistics; How to sight in your scope at different distances